A Comprehensive Training Initiative for Educators to Develop and Implement Effective Anti-Bullying Policies in K–12 Schools. Issue 2 (3rd April 2019) - Williford, Anne; Fite, Paula J.; DePaolis, Kathryn J.; Cooley, John L.; Hawley, Patricia H.; Isen, Debbie
Abstract: Although most states across the United States have enacted anti-bullying legislation, state laws vary greatly in detail and direction, leaving many school districts wondering how to best address the problem of bullying and comply with their state's legislative requirements. In response, a comprehensive, statewide training initiative was conducted for school personnel to offer guidance on developing and implementing such policies at the local level. In the present piece, the authors explicate the process by which they (a) derived theoretically grounded, empirically driven recommendations; (b) developed training materials and a project website; and (c) disseminated the material and recommendations across the state. They also present key outcomes as a result of this training initiative.